Key Dissemination Learnings from an Innovative, Value-Based Emergency Department Prevention Program - Rohie Marshall (Asia Pacific Journal of Health Management)
The Caboolture and Redcliffe regions of North Brisbane have experienced rapid population growth in recent years, with high levels of emergency department (ED) use, an ageing population, and a high proportion of complex health and psychosocial needs.